Pengabdian Masyarakat melalui Penyuluhan Kesehatan, Literasi Digital, dan Pengembangan Perpustakaan di Desa Sanrobone Kabupaten Takalar - Aulia Mahardhika; Dhian Karina A. Hattah; Harry Supratama (FKIP, Universitas Palangka Raya, 2024)
This community service journal discusses the involvement of Universitas Muslim Indonesia (UMI) in addressing social issues, particularly in its partner villages, including Sanrobone Village in Takalar Regency. As part of UMI’s commitment to the Tri Dharma of higher education, which includes community service, new faculty members are assigned to contribute to the development of underprivileged areas. The program aims to improve community welfare through educational outreach, health initiatives, and literacy programs. The community service activities in Sanrobone, which took place from July 3 to August 3, 2024, involved three UMI faculty members: Aulia Mahardika, dr. Harry Supratama, and dr. Dhian Karina A. Hattah. The primary focus of these activities included health education, digital literacy, and contributing to the establishment of a community library. The service program was designed to enhance the community's understanding of osteoporosis, intestinal worms, and the importance of digital literacy in today’s technological age. Additionally, the faculty members contributed to building a library in the village to foster reading habits and knowledge acquisition. The journal also highlights the collaboration with the local government, emphasizing the importance of integrating academic expertise into community-based development. The outcomes of this community service initiative not only supported the local community's development but also provided valuable learning experiences for the faculty, contributing to their professional growth as educators and community leaders.